Seminoma in a Transverse Testicular Ectopia: A Rare Case Report. (July 2020) - Altay, Canan; Kefi, Aykut; Tuna, Burcin; Secil, Mustafa
Transverse testicular ectopia (TTE) is an extremely rare congenital anomaly of the testis, characterized by migration of one testis toward the contrary hemiscrotum. TTE is usually associated with other testicular abnormalities such as persistent Mullerian duct syndrome, hypospadias, true hermaphroditism, and scrotal anomalies. Testicular sonography is the main initial diagnostic modality, followed by magnetic resonance imaging of the scrotum. These imaging modalities are important for determination of TTE and characterization of the testicular lesions. This case report provides the high-resolution ultrasonography, Doppler ultrasonography, magnetic resonance imaging, and diffusion-weighted imaging findings of a young man with seminoma in the transverse testicular ectopia. In addition, data on tumor stiffness, obtained with point shear-wave sonoelastography, are presented.